The Effectiveness Of Giving Angkak And Bananas Against Anemia In Children - Wati; Feva Tridyawati (International Journal of Health and Pharmaceutical (IJHP), 2022)
Iron is an important nutrient for making Hb, which is a protein in red blood cells that carries oxygen throughout the body's tissues and organs. Iron deficiency can be treated easily and inexpensively. Consuming two bananas a day is an alternative that can meet the needs of iron intake for anemic patients. This study aims to determine the effectiveness of giving Angkak and bananas to anemia in children at PMB Wati in 2021. The design of this study was a descriptive Quasy Experiment, with a two group only pre-post test design. The study involved 2 groups, namely the no-treatment group (added blood) and the treatment group (given added blood and bananas and Angkak). This research data is primary data. This instrument consists of two parts, namely the procedure sheet for giving bananas and Angkak and the action of checking Hb. In this study, the data analysis technique was carried out in two stages of calculation, successively, namely the normality test of the sample data with the Shapiro-Wilk test, and the faired sample test. All calculations were carried out with the help of SPSS for Windows software. Prior to data analysis, using a test on non-parametric statistics. The normality test of the research data used the Shapiro Wilk test. The results of the study were p-value 0.000 < 0.05, meaning that the addition of blood plus bananas and red rice was more effective in increasing hemoglobin levels in anemic children. The conclusion showed that there was a change (increase) in hemoglobin levels after being given treatment to the two groups, namely the added blood group plus bananas and Angkak.